TAX E-FILING AND TAX COMPLIANCE IN TEN YEARS: A BIBLIOGRAPHY APPROACH - Diana Airawaty; Wahyu Widarjo ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2021)
This study aims to review the researches on electronic tax filing which have affects to Tax Compliance in accredited scientific journal for 10-year period. The review was conducted against 99 articles relating to e-filing and tax compliance in various countries. The observation period started from 2010 – 2019. This examination used "Charting the field" and "analyzing the community-citation”. The first approach was mapping area includes the selection of articles; Classification of articles by topic, Method and discipline; Journal characteristics; and article characteristics. The second approach, the community analysis of tax scientists in the accounting area through the number of citations. Mendeley and Google Scholar were used to support this study. The research topic of e-Filing taxation revolved around the information technology in taxation system and tax compliance. Most of the researches used quantitative research methods and analysis tools of regression and Structural Equation Modeling (SEM). The survey method was dominant in this study, followed by study of literature. The variables were mostly from Technology Acceptance Model and UTAUT model meanwhile journal resources were from various journals and conferences. The analysis of citation showed that taxation researches already have contributions in accounting especially in taxation science. Next research should Increase the number of papers for further observation.